(untitled) (Research, Society and Development, 2022)
Introduction: Adverse Food Reactions (AAR) are any abnormal reaction to the ingestion of food or food additives, regardless of their cause. It is known that the gastrointestinal tract (GIT) is the gateway for nutrients from our food, and when it has its permeability altered, it can have as one of the consequences a food hypersensitivity, often undiagnosed, which causes numerous impacts, among these, alterations in the Central Nervous System, giving rise, influencing or worsening neurodevelopmental disorders Objective: To analyze how food hypersensitivity can influence disorders, mainly of a behavioral nature. Methodology: This is a literature review with a deductive approach. Results: From the literature study, it was possible to observe the importance of adequate nutrition for the homeostasis of the Central Nervous System, and in the prevention, treatment and promotion of pathologies in this System. Discussion of results: The importance of understanding the mechanisms of hypersensitivity for a better elucidation of its role in CNS pathologies was presented. In order to better determine the role of nutrition in these types of pathologies. Conclusion: The development of the present study made it possible to elucidate that neuronal pathologies have multifactorial causes, with hypersensitivity being a factor that may be part of this causal chain. A poor diet can give rise to both pathophysiologies, so it should be seen as an essential tool to break this pathological chain, in addition to the fact that adequate food is essential to meet the physiological needs and individuals to achieve homeostasis.